Crisis? What Crisis? Political articulation and government in the March of Tuscany through placita and diplomas from Guy of Spoleto to Berengar II - Santos Salazar, Igor (Reti Medievali Rivista, 2016)
In the last decades, much work have been done to deconstruct the mechanisms of government in Early Medieval Europe. In that task, the interpretation of the settlement of disputes and royal/imperial diplomas as the basis of the central government strategies in local spheres has been underlined by recent historiography. Following this methodology, the aim of this article is, thus, to analyze the mechanisms of governance in the March of Tuscany in a time characterized by political fluidity, focusing in the role played by the kings and lay and ecclesiastical aristocracies in the construction of complex political systems.